Three speakers’ perspectives on experience in Taylor Swift’s selected lyrics from Folklore album (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2022)
Pop songs are now an important means of expression for the modern generation. Academicians must consider this phenomenon as the object of language studies. This research attempts to analyze three songs in a Grammy-winning album of 2021, Folklore. Song lyrics in Betty, Cardigan, and August, written by Taylor Swift have the quality of narrative poetry (ballads) for having the characteristics of storytelling voiced by a different speaker in each song. The purpose of this research is to show how the varying amounts of transitivity process types in each lyric suggest different perspectives on reality. It uses a stylistic approach to expose the linguistic features that allow the speakers to portray diverse perspectives after going through a difficult relationship. As he apologizes to his partner, the speaker in Betty uses material process significantly to reconstruct the outer experiences. In Cardigan, the speaker emphasizes mental processes, incorporating her personal experience into her knowledge and memory. However, in August, the speaker uses both material and relational processes in equal proportions as she battles with her status in the relationship. Hence, listeners could identify with the various speakers' individual experiences as expressed in the lyrics.